Tingkat sosial ekonomi tidak berhubungan dengan kurang energi kronis (KEK) pada ibu hamil - Indriany Indriany; Siti Helmyati; Bunga Astria Paramashanti (Alma Ata University Press, 2014)
ABSTRACTBackground: Chronic energy deficiency (CED) has been experienced in almost all countries, especially in developing countries such as Bangladesh, India, Indonesia, Myanmar, Nepal, Srilanka, and Thailand. There are several cause factors of CED, one of them is socioeconomic level such as education, employment, knowledge, and family income.Objectives: To analyze the relationship between socioeconomic level and CED in Sedayu Subdistrict, Bantul,Yogyakarta.Methods: This was an observational study with cross sectional design. Population were all pregnant women in Sedayu Subdistrict. Samples were selected by using total sampling methods with total sample 201 pregnant women. Data were analyzed by using univariate analysis (descriptive), bivariat (chi-square), and multivariat (multiple logistic regression).Results: There were no significant relationship between maternal education (p=0.167, RP=1.55, 95% CI:0.84-2.87), maternal employment (p=0.360, RP=1.33, 95% CI:0.72-2.44), maternal knowledge (p=0.892, RP=0.96, 95% CI:0.49-1.85) and CED in pregnant women at Sedayu Subdistrict. However, there was significant relationship between family income with CED in pregnant woman (p=0.004, RP=2.73, 95% CI:1.31-5.68). Multivariat analysis showed that there was significant relationship between family income with CED in pregnant women (R2=0.08, OR=3.22, 95% CI:1.28-8.11). Low family income had a 3.22 times higher chance to incidence of CED in pregnant women.Conclusions: Sosioeconomic status such as education, employment, knowledge did not associate with CED in pregnant women. However, there was significant association in family income of pregnant women with CED and non CED.KEYWORDS: chronic energy deficiency, maternal education, employment, maternal knowledge, family income ABSTRAKLatar belakang: Kurang energi kronis (KEK) dialami oleh hampir semua negara khususnya di negara-negara berkembang seperti Bangladesh, India, Indonesia, Myanmar, Nepal, Srilanka, dan Thailand. Salah satu faktor yang dapat mempengaruhi KEK pada ibu hamil adalah tingkat sosial ekonomi seperti pendidikan ibu, pengetahuan ibu, pekerjaan ibu, dan pendapatan keluarga.Tujuan: Untuk mengetahui hubungan antara tingkat sosial ekonomi dengan kejadian KEK pada ibu hamil di Kecamatan Sedayu, Bantul, Yogyakarta.Metode: Jenis penelitian ini adalah observasional dengan desain cross sectional. Populasi penelitian adalah seluruh ibu hamil yang ada di Kecamatan Sedayu. Pemilihan sampel menggunakan total sampling dengan jumlah sampel 201 ibu hamil. Data dianalisis dengan menggunakan analisis univariat (deskriptif), bivariat (chi-square), dan multivariat (regresi logistik).Hasil: Hasil analisis menunjukkan tidak ada hubungan antara pendidikan ibu (p=0,17, RP=1,55, 95% CI:0,84-2,87), pekerjaan ibu (p=0,36, RP=1,33, 95% CI:0,72-2,44), dan pengetahuan ibu (p=0,83, RP=0,96, 95% CI:0,49-1,85) dengan kejadian KEK pada Ibu hamil. Namun demikian, terdapat hubungan yang signifikan antara pendapatan keluarga dengan KEK ibu hamil (p=0,004, RP=2,73, 95% CI:1,31-5,68). Analisis multivariat menunjukkan bahwa pendapatan keluarga mempunyai hubungan dengan kejadian KEK pada ibu hamil (R2=0,08, OR=3,22, 95% CI:1,28-8,11), pendapatan keluarga yang rendah memiliki peluang 3,22 kali untuk mengalami kejadian KEK pada ibu hamil.Kesimpulan: Tingkat sosial ekonomi seperti pendidikan, pekerjaan, pengetahuan ibu tidak berhubungan dengan KEK pada ibu hamil, namun pendapatan keluarga memiliki hubungan yang bermakna secara signifikan antara ibu hamil KEK dan tidak KEK.KATA KUNCI: kurang energi kronis, pendidikan, pekerjaan, pengetahuan, pendapatan keluarga